Pengaruh Dukungan Sosial Teman Sebaya Terhadap Minat Belajar Peserta Didik Kelas XI di SMA N 1 Dua Koto Kabupaten Pasaman - Utia Rahma; Fifi Yasmi; Yasrial Chandra (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2021)
The study is on the bakground by still lack the influence of peer social support on the learning interest of XI high school protester 1 two villagw pasaman. There is still a phenomenon in the field, symptoms indicating a low interest in learning participants. The purpose of this study is to test the impact peer social support has on the learning interest of the XI class educated in the two passafs districk koto. This type of research is a carbon-descriptive cumulative. The research population is all the sophomines in the state high school 1 second listen koto in the second semester of 2019/2020 for 228 people. The sample is taken by a sample proportionately fandom sampling technique, sample number70, data collection using angket, data analysis using descriptive statistics with percentages and testing correlation. Studies reveral that: (1) social support of peers falls into sufficients categories okay. (2) the interests of learners fall into moderate categiries. (3) found A positive and significant influence between peer social support for the learning interests of learners. It is recommended to learners to increase social support among peers so that interest in learning can increase in the future.